Effect of aromatic substituents on thermoresponsive functional polycaprolactone micellar carriers for doxorubicin delivery - Wang, Hanghang; Polara, Himanshu; Bhadran, Abhi; Shah, Tejas; Babanyinah, Godwin Kweku; Ma, Ziyuan; Calubaquib, Erika L.; Miller, Justin T.; Biewer, Michael C.; Stefan, Mihaela C. (Frontiers in Pharmacology, 2024)
polycaprolactone, amphiphilic diblock copolymers, thermoresponsive polymers, polymeric micelles, drug delivery ABSTRACT. Amphiphilic functional polycaprolactone (PCL) diblock copolymers are excellent candidates for micellar drug delivery. The functional groups on the backbone significantly affect the properties of PCL. A systematic investigation of the effect of aromatic substituents on the selfassembly of -functionalized PCLs and the delivery of doxorubicin (DOX) is presented in this work. Three thermoresponsive amphiphilic diblock copolymers with poly(-benzyloxy-caprolactone) (PBnCL), poly(-phenyl--caprolactone) (PPhCL), poly(-(4-ethoxyphenyl)-caprolactone) (PEtOPhCL), respectively, as hydrophobic block and -tri(ethylene glycol) functionalized PCL (PME3CL) as hydrophilic block were prepared through ring-opening polymerization (ROP). The thermoresponsivity, thermodynamic stability, micelle size, morphology, DOX-loading, and release profile were determined. The LCST values of amphiphilic diblock copolymers PME3CL-b-PBnCL, PME3CL-b-PPhCL, and PME3CL-b-PEtOPhCL are 74.2 °C, 43.3 °C, and 37.3 °C, respectively. All three copolymers formed spherical micelles in phosphate-buffered saline (PBS, 1×, pH = 7.4) at low concentrations ranging from 8.7 × 10 -4 g/L to 8.9 × 10 -4 g/L. PME3CL-b-PBnCL micelles showed the highest DOX loading capacity of 3.01 ± 0.18 (wt%) and the lowest drug release, while PME3CL-b-PEtOPhCL micelles exhibited the lowest DOX loading capacity of 1.95 ± 0.05 (wt%) and the highest drug release. Cytotoxicity and cellular uptake of all three micelles were assessed in vitro using MDA-MB-231 breast cancer cells. All three empty micelles did not show significant toxicity to the cells at concentrations high up to 0.5 mg/mL. All three DOX-loaded micelles were uptaken into the cells, and DOX was internalized into the nucleus of the cells.The thermoresponsivity, thermodynamic stability, micelle size, morphology, DOX-loading, and release profile were determined. Cytotoxicity and cellular uptake were assessed in vitro using MDA-MB-231 breast cancer cells.Commented [HP1]: The author's name was corrected.